2013
DOI: 10.1126/scisignal.2003638
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Reactive Oxygen Species Promote Epidermal Differentiation and Hair Follicle Development

Abstract: Proper regulation of keratinocyte differentiation within the epidermis and follicular epithelium is essential for maintenance of epidermal barrier function and hair growth. The signaling intermediates that regulate the morphological and genetic changes associated with epidermal and follicular differentiation remain poorly understood. We tested the hypothesis that reactive oxygen species (ROS) generated by mitochondria are an important regulator of epidermal differentiation by generating mice with a keratinocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
261
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(280 citation statements)
references
References 56 publications
19
261
0
Order By: Relevance
“…The signaling pathways associated with this phenomenon are incompletely understood. However, mitochondrial oxidative stress was shown to promote epidermal differentiation in mice (40) and in culture (41), as did uncoupled mitochondria (42). Our studies of constitutive Sod2-deficient mice also showed increased keratinocyte differentiation (19), but early lethality complicated interpretation of this result.…”
Section: Discussionmentioning
confidence: 50%
“…The signaling pathways associated with this phenomenon are incompletely understood. However, mitochondrial oxidative stress was shown to promote epidermal differentiation in mice (40) and in culture (41), as did uncoupled mitochondria (42). Our studies of constitutive Sod2-deficient mice also showed increased keratinocyte differentiation (19), but early lethality complicated interpretation of this result.…”
Section: Discussionmentioning
confidence: 50%
“…Although ROS have long been known for their damage-promoting detrimental effects, their roles as signaling molecules are now becoming better understood (Shadel and Horvath, 2015). In particular, mitochondrial ROS (mtROS) signaling has also been implicated in homeostatic processes, including cellular differentiation (Hamanaka and Chandel, 2010;Tormos et al, 2011;Hamanaka et al, 2013). A recent study demonstrated that multipotent neural progenitors maintain a high level of ROS (Le Belle et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ROS have been implicated in a variety of processes such as reducing lifespan of hematopoietic stem cells, 89 inducing insulin resistance in adipocytes, 90 and regulating Notch signaling in epidermal cell differentiation. 91 Recent work comparing chain addition and thiol-ene polymerizations for encapsulation of primary chondrocytes shows that increased ROS exposure resulting from chain addition polymerizations leads to hypertrophic chondrocyte phenotypes similar to pathologic chondrocytes observed in osteoarthritis. In contrast, the phenotypes of chondrocytes encapsulated using a thiol-ene polymerization resemble those present in hyaline cartilage.…”
Section: Resultsmentioning
confidence: 99%